A low-temperature copper-carbon composite material, its preparation method, its application and usage.
By using low-temperature copper-carbon composite materials and combined with micro-nano bubble treatment, the existing advanced oxidation technology has solved the complex operation, high cost and insufficient anti-interference ability of the water organic pollutants, and achieved efficient, economical and widely applicable organic pollutant removal effect.
Patent Information
- Application Number
- CN202310196292.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-03-03
AI Technical Summary
The existing advanced oxidation technology has complex operations when removing organic pollutants in water bodies, which may lead to secondary pollution or high operating costs, and is easily disturbed by pH, anions and natural organic matter, making it difficult to actually apply.
Low-temperature copper-carbon composite material is used, which consists of biomass and copper salts, prepared by ball mill mixing and pyrolysis, has a wide range of pH adaptability and anti-interference ability, and significantly improves the removal efficiency of organic pollutants under micro-nano bubble treatment.
Low-temperature copper-carbon composite materials maintain high-efficiency removal ability within a wide pH range, strong anti-interference ability, low preparation cost and high yield, and are suitable for organic pollutant treatment in complex water environments.
Smart Images

Figure CN116078381B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic pollutant degradation, and in particular to a low-temperature copper-carbon composite material, a preparation method, a use method and applications thereof. Background Art
[0002] With the development of the medical industry, the abuse of antibiotics has caused the problem of organic pollution in water bodies to become increasingly serious worldwide. Organic pollution has hazards that cannot be ignored and is an environmental problem that needs to be solved urgently. At present, the treatment methods for organic pollution mainly include chemical oxidation, biodegradation, adsorption, ion exchange, etc. Among them, advanced oxidation is a treatment method for organic pollution.
[0003] In the prior art, various advanced oxidation technologies have been proposed, including Fenton reaction, electrochemical oxidation and photooxidation (including photolysis and photocatalysis) to remove organic pollutants from water. However, on the one hand, it has problems such as complex operation, possible secondary pollution or high operating costs, which make it difficult to apply in practice; on the other hand, it is seriously affected by pH and various anions and natural organic matter in water during the application process, which makes molecular oxygen activation difficult to apply in practice. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a low-temperature copper-carbon composite material, a preparation method, a use method and its application that can efficiently remove organic pollutants. On the one hand, it overcomes the problem that the composition is easily affected by pH value, various anions and natural organic matter, and on the other hand, it solves the problems of high energy consumption, high cost and low yield in preparation.
[0005] First, the present invention provides a low-temperature copper-carbon composite material, including the following raw materials: biomass and copper salt, the mass ratio of the two is 1-4:1; wherein the biomass is a mixture of one or more of peanut shells, wood shavings, ramie and straw, the particle size of the biomass is 100-200 meshes, and the copper salt is a mixture of one or more of copper nitrate trihydrate, copper chloride dihydrate and copper sulfate monohydrate.
[0006] Secondly, the present invention also provides a method for preparing the low-temperature copper-carbon composite material as described above, comprising the following steps:
[0007] S1. mixing the naturally air-dried, ground and sieved biomass with copper salt in a ball mill, wherein the mass ratio of the biomass to the copper salt is 1 to 4:1;
[0008] S2. placing the mixture into a furnace for pyrolysis in a rare gas atmosphere or a nitrogen atmosphere, wherein the pyrolysis heating rate is 2 to 10°C / min, the pyrolysis temperature is 200 to 300°C, and the pyrolysis time is 1 to 3h;
[0009] S3. Cool naturally to room temperature to obtain a low-temperature copper-carbon composite material.
[0010] The rotation speed of the ball milling is 300-500 rpm, the pyrolysis heating rate is 4-7°C / min, the pyrolysis temperature is 240-270°C, and the pyrolysis time is 1.5-2.5h.
[0011] Again, the present invention also provides a method for using the low-temperature copper-carbon composite material as described above, adding the low-temperature copper-carbon composite material to organic pollutants in water / adding it to an aqueous solution of organic pollutants, mixing it, and then subjecting it to micro-nano bubble treatment, and leaving it to react until the reaction is completed; wherein, the pressure value of the air inlet valve of the micro-nano bubbles is 0.2MPa~0.6MPa, the gas of the micro-nano bubbles is air or oxygen or ozone, and the ventilation time of the micro-nano bubbles is 5~20min.
[0012] Wherein, the content of the low-temperature copper-carbon composite material in the water body organic pollutant / the aqueous solution of organic pollutant is greater than 0.3 g / L.
[0013] Furthermore, the pressure value of the air inlet valve of the micro-nano bubbles is 0.3MPa-0.5MPa, the gas of the micro-nano bubbles is air, and the ventilation time of the micro-nano bubbles is 7-12min.
[0014] Finally, the present invention also provides an application of the low-temperature copper-carbon composite material as described above in molecular oxygen activation and degradation of organic pollutants in water.
[0015] The technical solution of the present invention has the following advantages:
[0016] In the present invention, biomass waste and copper salt are used as raw materials, which greatly reduces the preparation cost and promotes the treatment of waste, and the material manufacturing process is simple and has strong operability; the prepared composite material has a wide pH application range, strong anti-interference ability for various anions and humic acid, and has the characteristics of targeting, and always has excellent water organic pollutant removal effect under the combined treatment of micro-nano bubbles. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 This is a SEM image of the low-temperature copper-carbon composite material prepared in Example 1;
[0019] Figure 2 This is the SEM image of the Scots pine wood shavings biochar prepared in Comparative Example 1;
[0020] Figure 3 Removal efficiency of ciprofloxacin by low-temperature copper-carbon composites under different pH conditions;
[0021] Figure 4 is the removal rate of ciprofloxacin by low-temperature copper-carbon composite material under different anion conditions;
[0022] Figure 5 This is a diagram showing the influence of humic acid on the catalytic effect of low-temperature copper-carbon composite materials. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all belong to the protection scope of the present invention. The experimental reagents and materials used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0024] First, the present application provides a low-temperature copper-carbon composite material, including the following raw materials: biomass and copper salt, the mass ratio of the two is 1 to 4:1; wherein the biomass is a mixture of one or more of peanut shells, wood shavings, ramie and straw, the particle size of the biomass is 100 to 200 meshes, and the copper salt is a mixture of one or more of copper nitrate trihydrate, copper chloride dihydrate and copper sulfate monohydrate.
[0025] The biomass raw materials used in this application are all biomass wastes, which are low-cost and promote waste treatment, thereby reducing the cost of preparing traditional biochar composite materials.
[0026] Secondly, the present application also provides a method for preparing the low-temperature copper-carbon composite material as described above, comprising the following steps:
[0027] S1. mixing the naturally air-dried, ground and sieved biomass with copper salt in a ball mill, wherein the mass ratio of the biomass to the copper salt is 1 to 4:1;
[0028] S2. placing the mixture into a furnace for pyrolysis in a rare gas atmosphere or a nitrogen atmosphere, wherein the pyrolysis heating rate is 2 to 10°C / min, the pyrolysis temperature is 200 to 300°C, and the pyrolysis time is 1 to 3h;
[0029] S3. Cool naturally to room temperature to obtain a low-temperature copper-carbon composite material.
[0030] The ball milling speed is 300-500 rpm, the pyrolysis heating rate is 4-7°C / min, the pyrolysis temperature is 240-270°C, and the pyrolysis time is 1.5-2.5h. Further, the mass ratio of the biomass to the copper salt is preferably 1:1, the ball milling speed is preferably 400 rpm, the pyrolysis temperature is preferably 255°C, the heating rate is preferably 6°C / min, and the pyrolysis time is preferably 2h. The above preparation method is relatively simple and highly operable.
[0031] The present application utilizes biomass waste and copper salt as raw materials to prepare copper-containing biochar composite materials at low temperature, which greatly reduces the preparation cost and improves the yield, and the material production process is simple and highly operable.
[0032] Again, the present application also provides a method for using the low-temperature copper-carbon composite material as described above, wherein the low-temperature copper-carbon composite material is added to the organic pollutants in the water body / added to the aqueous solution of the organic pollutants, mixed and treated with micro-nano bubbles, and left to react until the reaction is completed; wherein the pressure value of the air inlet valve of the micro-nano bubbles is 0.2MPa to 0.6MPa, the gas of the micro-nano bubbles is air or oxygen or ozone, and the ventilation time of the micro-nano bubbles is 5 to 20min. wherein the content of the low-temperature copper-carbon composite material in the organic pollutants in the water body / the aqueous solution of the organic pollutants is greater than 0.3g / L.
[0033] Furthermore, the pressure value of the air inlet valve of the micro-nano bubbles is 0.3MPa-0.5MPa, the gas of the micro-nano bubbles is air, and the ventilation time of the micro-nano bubbles is 7-12min. Specifically, the ventilation is preferably 10min, and the pressure value of the air inlet valve is preferably 0.4MPa.
[0034] This composite material has a strong anti-interference ability against various anions and humic acid. It not only has the characteristics of targeting, but also has a good removal effect on organic pollutants in water under air treatment.
[0035] Finally, the present application also provides an application of the low-temperature copper-carbon composite material as described above in molecular oxygen activation and degradation of organic pollutants in water bodies. The low-temperature copper-carbon composite material is particularly suitable for removing ciprofloxacin from a ciprofloxacin solution.
[0036] Example 1
[0037] Scotch pine wood shavings are used as biomass raw materials, and cupric chloride dihydrate is used as copper salt raw material.
[0038] Take 3g of naturally air-dried and ground sieved 100-mesh and 200-mesh pine wood shavings powder, mix it with 3g of copper chloride dihydrate; then put the two into a ball mill and mill them at a speed of 300rpm for 40min to obtain a mixture; place the mixture in a tube furnace, heat it at a rate of 5℃ / min under nitrogen conditions, keep the temperature at 250℃ for 1h, and cool it naturally after the reaction to obtain 3.68g of low-temperature copper-carbon composite material, recorded as Cu-WSBC. After testing, the yield of the low-temperature copper-carbon composite material is 80%, indicating that the preparation method has a high yield.
[0039] The scanning electron microscope image of the low-temperature copper-carbon composite material (Cu-WSBC) obtained in this example is as follows Figure 1 As shown, from Figure 1 It can be seen that the copper particles are successfully loaded on the biochar (the particles on the surface are copper particles)
[0040] Example 2
[0041] Peanut shells are used as biomass raw materials, and copper sulfate monohydrate is used as copper salt raw material.
[0042] Take 2g of peanut shell powder between 100 mesh and 150 mesh after natural air drying and grinding and sieving, mix it with 1g of copper sulfate monohydrate; then put the two into a ball mill and ball mill at a speed of 400rpm for 60min to obtain a mixture; place the mixture in a tubular furnace, heat it at a rate of 2℃ / min under nitrogen conditions, maintain the temperature for 1h after reaching 300℃, and obtain 2.42g of low-temperature copper-carbon composite material after natural cooling after the reaction is completed.
[0043] Example 3
[0044] Ramie is used as biomass raw material, and copper chloride dihydrate is used as copper salt raw material
[0045] 3 g of ramie powder between 150 mesh and 200 mesh after natural air drying and grinding and sieving was mixed with 1 g of copper chloride dihydrate; then the two were put into a ball mill and ball milled at a speed of 500 rpm for 20 minutes to obtain a mixture; the mixture was placed in a tube furnace and heated at a rate of 10 ° C / min under nitrogen conditions, and the temperature was maintained at 200 ° C for 3 hours. After the reaction was completed, it was cooled naturally to obtain 3.81 g of low-temperature copper-carbon composite material.
[0046] Comparative Example 1
[0047] Only Scots pine shavings are used as raw material.
[0048] Take 3g of naturally air-dried and ground sieved pine wood shavings powder between 100 and 200 meshes, place it in a ball mill at 300rpm for 40min; then place it in a tube furnace, heat it at a rate of 5℃ / min under nitrogen conditions, and keep the temperature at 250℃ for 1h; after the reaction is completed and cooled naturally, the final pine wood shavings biochar is obtained, which is recorded as WSBC. Its scanning electron microscope image is as follows Figure 2 As shown, from Figure 2 It can be seen that there is no copper particle loaded on the surface of biochar.
[0049] Experimental Example 1
[0050] 15 mg of the low-temperature copper-carbon composite material (Cu-WSBC) prepared in Example 1 and 35 mg of hydroxylamine hydrochloride, 15 mg of the wood shavings biochar (WSBC) prepared in Comparative Example 1 and 35 mg of hydroxylamine hydrochloride, and 40 mg / L of Cu were added to three beakers respectively. 2+ and 35 mg of hydroxylamine hydrochloride; then 50 mL of 10 mg / L ciprofloxacin solution was added to each of the three beakers, and micro-nano bubble treatment was performed, followed by reaction for 60 minutes. The test results are shown in Table 1.
[0051] Table 1 Removal rate of ciprofloxacin by different materials
[0052]
[0053] As shown in Table 1, the catalytic removal rate of ciprofloxacin in water by Cu-WSBC prepared by the present invention is as high as 93.8% within a reaction time of 60 minutes, which is far superior to the catalytic effect of simple Scotch pine shavings biochar (WSBC) on the one hand, and on the other hand, compared with the simple addition of Cu 2+ It also showed better catalytic performance; the above proves that the low-temperature copper-carbon composite material prepared in this application is a low-cost composite material for efficiently removing ciprofloxacin.
[0054] Experimental Example 2
[0055] 15 mg of Cu-WSBC prepared in Example 1 and 35 mg of hydroxylamine hydrochloride were placed in a beaker containing 50 mL of ciprofloxacin (10 mg / L) and treated with micro-nano bubbles. Then, the experiment was carried out at pH values of 3, 5, 7, 9, and 11. After 60 min of reaction, the removal related data were recorded as follows: Figure 3 shown.
[0056] from Figure 3It can be seen that under different pH conditions, the low-temperature copper-carbon composite material of the present invention achieves efficient degradation of ciprofloxacin; thus, it can be seen that the low-temperature copper-carbon composite material prepared by the present invention is a catalyst with good stability in a wider pH range, and has great potential in the application of removing organic pollution from actual water bodies.
[0057] Experimental Example 3
[0058] 15 mg of Cu-WSBC prepared in Example 1 and 35 mg of hydroxylamine hydrochloride were placed in a beaker containing 50 mL of ciprofloxacin (10 mg / L) and subjected to micro-nano bubble treatment. Then, the mixture was stirred at 4 °C in the presence of Cl- (1 mmol / L), H 2 PO 4 -(1mmol / L), HCO 3 -(1mmol / L) coexistence, the reaction time was 60min, and the removal related data were recorded. Figure 4 shown.
[0059] from Figure 4 It can be seen that the addition of different anions has little effect on the removal of ciprofloxacin by Cu-WSBC molecular oxygen activation; this shows that the low-temperature copper-carbon composite material has good anti-interference ability for different anions, and the low-temperature copper-carbon composite material has the potential to be applied to complex water matrices.
[0060] Experimental Example 4
[0061] 15 mg of Cu-WSBC prepared in Example 1 and 35 mg of hydroxylamine hydrochloride were placed in a beaker containing 50 mL of ciprofloxacin (10 mg / L) and subjected to micro-nano bubble treatment. Then, the experiment was carried out in the presence of 20 mg / L of humic acid (HA) for 60 min, and the removal data were recorded as follows: Figure 5 shown.
[0062] analyze Figure 5 It can be seen that after adding 20 mg / L humic acid (HA), it has little effect on the molecular oxygen activation and removal of ciprofloxacin by the low-temperature copper-carbon composite material; this shows that the low-temperature copper-carbon composite material has good anti-interference ability for natural organic matter, and the low-temperature copper-carbon composite material is a catalytic material with targeted characteristics.
[0063] In summary, the low-temperature copper-carbon composite material provided in the present application has excellent treatment efficiency in the treatment of organic pollution in water bodies, has a wide pH application range, has strong anti-interference ability for various anions and humic acid, and has targeted characteristics. It always has excellent removal effect of organic pollutants in water bodies under the combined treatment of micro-nano bubbles.
[0064] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for using a low-temperature copper-carbon composite material, characterized in that: The low-temperature copper-carbon composite material and hydroxylamine hydrochloride are added to the aqueous solution of the organic pollutant, mixed, and then treated with micro-nano bubbles, and left to stand until the reaction is completed; wherein the pressure value of the air inlet valve of the micro-nano bubbles is 0.2MPa~0.6MPa, the gas of the micro-nano bubbles is air or oxygen or ozone, and the ventilation time of the micro-nano bubbles is 5~20min; The content of the low-temperature copper-carbon composite material in the aqueous solution of the organic pollutant is greater than 0.3 g / L, the mass ratio of the low-temperature copper-carbon composite material to hydroxylamine hydrochloride is 15:35, and the organic pollutant is ciprofloxacin; The preparation method of the low-temperature copper-carbon composite material comprises the following steps: S1. mixing the naturally air-dried and ground biomass with copper salt by ball milling, wherein the mass ratio of the biomass to the copper salt is 1-4:1; S2. placing the mixture into a furnace and pyrolyzing it under a nitrogen atmosphere, wherein the pyrolysis heating rate is 2-10°C / min, the pyrolysis temperature is 200-300°C, and the pyrolysis time is 1-3h; S3. Naturally cool to room temperature to obtain a low-temperature copper-carbon composite material; Wherein, the rotation speed of the ball milling mixing is 300-500 rpm; The biomass is a mixture of one or more of peanut shells, wood shavings, ramie and straw, the particle size of the biomass is 100-200 meshes, and the copper salt is a mixture of one or more of copper nitrate trihydrate, copper chloride dihydrate and copper sulfate monohydrate.
Citation Information
Patent Citations
Method for preparing ozone catalyst for removal of antibiotics in water by using cheap material as carrier
CN108404913A
Method for treating salt-containing degradation-resistant wastewater by activating peroxymonosulfate with biochar-copper oxide composite material
CN112194236A
Low-temperature iron-carbon composite material as well as preparation method and application thereof
CN114950429A